VIOLENCE AGAINST ELDERLY PEOPLE WITH SPECIAL REFERENCE TO GRANDMOTHER SLAVE SYNDROME (Heritage, 2024)
Violence in the family is an increasing legal and sociological problem. As part of this domestic violence, there are various manifestations of violence, and women, men, children and the elderly can be found in the position of victims, but men appear in the rarest number of cases. Violence in the family can be manifested in different ways, and the violence itself does not always have to involve the use of physical force, but can consist of psychological violence, economic violence and other forms of denial of certain rights.In the paper, the author deals with the problem of violence against the elderly within the framework of the problem of family violence, with special attention to one of the most prevalent forms of violence and exploitation of the elderly, known as the "slave grandmother" syndrome. The paper will also give concrete examples from practice with reference to court practice and the actions of competent authorities in such and similar situations.
Keywords: violence, elderly, children, parents, grandmother slave